2017
DOI: 10.1177/0146167217742886
|View full text |Cite
|
Sign up to set email alerts
|

The Reputational Consequences of Generalized Trust

Abstract: The present research examines the reputational consequences of generalized trust. High-trust individuals are seen as moral and sociable, but not necessarily competent. When controlling for other traits, there is a negative relationship between trust and perceived competence (Studies 1 and 2). Compared with optimism, generalized trust has stronger effects on morality and sociability (Study 2). Furthermore, people judge those who do not discriminate between trustworthy and untrustworthy groups (unconditional tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 72 publications
(117 reference statements)
4
12
0
Order By: Relevance
“…In both Experiments 1 and 3, judges considered more (vs. less) optimistic forecasters warmer, even when they were less confident. These results are in line with previous work documenting the positive effect of dispositional optimism on inferences of warmth (e.g., Evans & van de Calseyde, ). Optimism may be related to the perception of warmth for multiple reasons: Optimists may be seen as having a strong desire to avoid hurting other people's feelings, which represents a central aspect of interpersonal warmth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In both Experiments 1 and 3, judges considered more (vs. less) optimistic forecasters warmer, even when they were less confident. These results are in line with previous work documenting the positive effect of dispositional optimism on inferences of warmth (e.g., Evans & van de Calseyde, ). Optimism may be related to the perception of warmth for multiple reasons: Optimists may be seen as having a strong desire to avoid hurting other people's feelings, which represents a central aspect of interpersonal warmth.…”
Section: Discussionsupporting
confidence: 92%
“…In the area of future business forecasts, valence might affect perceptions of warmth and morality. A generally optimistic worldview and smiling behavior are associated with perceptions of warmth and morality (Evans & van de Calseyde, 2017;Vollmann, Renner, & Weber, 2007;Wang, Mao, Li, & Liu, 2017). Thus, optimistic forecasters may be seen as more friendly, likeable, and well-intentioned.…”
Section: Perceptions Of Warmth Morality and Competencementioning
confidence: 99%
“…Moreover, the gullible face was also seen as more trustworthy and less dominant than the anti-gullible face. These findings are in line with the notion that gullible people are seen as well-intentioned and harmless individuals (Evans & van de Calseyde, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Second, we examine relationships between gullibility impressions and impressions of trustworthiness and dominance. Prior work suggests that gullible people are seen as wellintentioned and approachable, but also as relatively incompetent (Evans & van de Calseyde, 2018). This view predicts that that gullible-looking people should score high on perceived trustworthiness (a proxy for an individual's perceived intentions), but low on perceived dominance (a proxy for an individual's ability to implement their intentions; Todorov, Said, Engell, & Oosterhof, 2008).…”
Section: Gullibility Impressionsmentioning
confidence: 99%
“…Nevertheless, we believe that usefulness ratings that we focus on in the present analyses can be considered a legitimate proxy of perceived trustworthiness of reviews. In terms of personperception, useful may be best described as related to competence (Hartley et al, 2016;Landy, Piazza, & Goodwin, 2016), which represents a component of perceived trustworthiness in models of trust (Mayer, Davis, & Schoorman, 1995) and shows positive empirical associations with perceptions of person trustworthiness (Evans & van de Calseyde, 2017;Landy et al, 2016). In addition, existing investigations of online product reviews showed that the associations between readers' perceptions of usefulness and trustworthiness are similar in strength to the associations that are typically found among different indicators of the same latent construct, e.g., r = .64 in Wu and Lin (2017).…”
Section: Discussionmentioning
confidence: 99%